Long‐term strength and deformational analysis of reinforced concrete columns - Simbirkin, Valery; Balevičius, Robertas (Journal of Civil Engineering and Management, 2004)
The paper presents a method of non‐linear analysis of load‐carrying capacity and deformations of reinforced concrete columns subjected to long‐term loads. Physical relationships expressing non‐linear relations between internal forces and stresses, strains and stiffness are derived on the basis of the fracture and creep theories for concrete and using non‐linear stress‐strain diagrams modified for time effects. Second‐order geometrical effects are taken into account by solving a second‐order differential equation for elements subjected to compression and bending. A number of numerical and test results are presented. The technique proposed is verified by comparison of analysis results with extensive experimental data.First Published Online: 14 Oct 2010